PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PICTURE AND PICTURE PADA MATERI PERJUANGAN PARA TOKOH DALAM PERLAWANAN TERHADAP BELANDA KELAS V SDN 2 JEUMPA ACEH BARAT DAYA - Wirdasni, Dian; Yamin, M.; Fitri, Aida (Elementary Education Research, 2024)
Abstract (English)This type of research is classroom action research that examines learning activities in the form of actions that are deliberately presented in the classroom. The Picture And Picture learning model is a learning method that applies pictures and pairs or sequences them in a logical arrangement. This study aims (1) To find out the teacher's activity in the learning process by applying the Picture And Picture cooperative learning model on the Material of the Struggle of the Figures in the Resistance Against the Dutch Class V SDN 2 Jeumpa Aceh Barat Daya, (2) To find out the activities of students and teachers in the learning process. learning by applying the Picture And Picture cooperative learning model on the Material of the Struggle of Figures in the Resistance Against the Dutch Class V SDN 2 Jeumpa Aceh Barat Daya. The subjects in this study were fifth grade students at SDN 2 Jeumpa Aceh Barat Daya. Data collection was carried out using: Observation sheets of teacher and student activities and tests. Data analysis uses simple statistics, namely percentages. According to data analysis, it was found: (1) the average teacher activity in the teaching and learning process cycle I was 2.6, and the moderate category was 3.5 in cycle II which was included in the good category. (2) the activeness of students in cycle I during the teaching and learning process averaged the value of the bad category 2.25, while the good category in cycle II was 3.37, and (3) student learning outcomes during the period of students increased, namely the percentage of students in cycle I became 60 % in cycle II learning success reached 88%.Abstrak Jenis penelitian ini adalah penelitian tindakan kelas yang mengkaji kegiatan pembelajaran berupa tindakan yang sengaja dihadirkan di dalam kelas. Model pembelajaran Picture And Picture yaitu metode pembelajaran yang menerapkan gambar dan memasangkan atau mengurutkannya dalam susunan yang logis. Penelitian ini bertujuan (1) Untuk mengetahui aktivitas guru pada proses pembelajaran dengan menerapkan model pembelajaran kooperatif Picture And Picture Pada Materi Perjuangan Para Tokoh Dalam Perlawanan Terhadap Belanda Kelas V SDN 2 Jeumpa Aceh Barat Daya, (2) Untuk mengetahui aktivitas siswa dan guru pada proses pembelajaran dengan menerapkan model pembelajaran kooperatif Picture And Picture Pada Materi Perjuangan Para Tokoh Dalam Perlawanan Terhadap Belanda Kelas V SDN 2 Jeumpa Aceh Barat Daya. Subjek dalam penelitian ini adalah siswa kelas V SDN 2 Jeumpa Aceh Barat Daya. Pengumpulan data dilakukan dengan menggunakan : Lembaran pengamatan aktivitas guru dan siswa dan Tes. Analisis data menggunakan statiktik sederhana yaitu persentase. Menurut analisis data didapatkan: (1) rata-rata aktivitas guru pada proses belajar mengajar siklus I sebesar 2,6, dan kategori sedang sebesar 3,5 di siklus II yang termasuk dalam kategori baik. (2) keaktifan siswa di siklua I selama proses belajar mengajar rata-rata nilai kategori buruk 2,25, sedangkan kategori baik pada siklus II 3,37, dan (3) hasil belajar siswa periode siswa meningkat yaitu persentase siswa pada siklus I menjadi 60% di siklus II keberhasilan belajar mencapai 88%.